Rock cut slope stability evaluation of the Crocker formation along Jalan UMS, Kota Kinabalu, Sabah - Mohd Muzhafar Mohd Zaki; Sanudin Tahir; Ismail Abd Rahim; Ahmad Norazhar Mohd Yatim (Universiti Malaysia Sabah, 2012)
The aim of this paper is to present the result of an evaluation of the cut rock slope stability of the Crocker Formation along Jalan UMS, Kota Kinabalu, Sabah. Geological mapping, discontinuity survey, and kinematic analysis have been conducted on ten (10) selected cut rock slopes in the study area. Result of kinematic analysis shows that wedge, toppling and planar failures are potential in five cut rock slopes. However, no potential modes of failure are identified in cut rock slopes numbers 2, 7, 8, 9 and 10. Flatten slope range from 30o to 55o , wire mesh and drainage ditches are proposed as mitigation measures for the cut rock slopes in the study area.